Quality Assessment of Electrical Equipment - Nutu, Catalin Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper is concerned with the methods of the measuring the quality and especially how the decision and game theory can be used in order to reach the goal of measuring quality in general and the quality of electrical equipment, in particular.